The Role of an Accountant in Detecting Corruption - Haryono Umar; Rahima Br Purba; Siti Safaria; Welda Mudiar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The increasing corruption has made Indonesia one of the countries in the red category (corrupt) globally. Corruption is an act to enrich oneself, other people, or corporations by violating the law or abusing authority the focus of this research is on the causes of fraud star corruption. The characteristics of corruption in Indonesia are very complex, abuse of power or authority, and not carried out with trust. Involving various elements from the government/private sector is the cause of fraud star corruption, this occurs in State/Regional Owned Enterprises (BUMN/D) and public officials from the center to the regions. This study discusses one of the contributions in fighting corruption in Indonesia, using a corruption detection model. To be free from the corruption epidemic in Indonesia, the introduction of the HU model consists of the variables lack of integrity (lack of integrity), opportunity (opportunity), pressure (pressure), rationalization (rationalization), and capability (capability) to give hope and get answers. The HU model proves that even the amount of pressure, the number of opportunities, the ease of justification, as well as a high position and authority will not encourage corruption if there is strong integrity. The result shows that the loss of integrity is the most dominant cause of people committing corruption. This study is also able to categorize agencies that are indicated as being corrupt (red), between indicated and not indicated (grey), and not indicated (green).